KONSENTRASI INDUSTRI PENGOLAHAN DI PROPINSI JAWA TENGAH - Nevita Sari (Economics Development Department, Universitas Negeri Semarang, Indonesia, 2014)
This study aims to determine how the concentration of investment, employment, and value added in the manufacturing sector in Central Java Province. The method of data analysis in this study using the analysis method or the concentration ratio CR4 and CR8. The data used is data investment, employment, and value added of the manufacturing sector in Central Java by using the 5-digit ISIC obtained from the Central Statistics Agency (BPS) of Central Java Province. The results showed that: (1) In calculating the analysis CR4 and CR8 concentration of industrial investment in Central Java during the period 2005-2009 has two types of market structure. (2) In calculating the concentration analysis CR4 and CR8 labor sector in Central Java during the period 2005-2009 have type 2 oligopoly market structure. (3) In calculating the concentration CR4 added value of industry sector in Central Java during the period 2005-2008 have full oligopoly market structure and concentration of the industry in the year 2009 in Central Java have shaped the market structure of oligopoly type 2, and by calculating the concentration of value-added CR8 industrial sector in Central Java during the period 2005-2009 have shaped the market structure of oligopoly type2.